Evaluasi Penampilan dan Efek Heterosis Hasil Persilangan Beberapa Aksesi Jarak Pagar (Jatropha curcas L.) - Wijaya, Andi; Susantidiana, ,; Harun, Muhamad Umar; Surahman, Memen (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Agronomic performance and heterosis effect of progeny are important criteria for selection of parental hybrid. Theagronomic performance evaluation of Jatropha progeny which was derived from crossing of some Jatropha accessions hasbeen carried out for those goals. The study was conducted at Agro Techno Park, Indralaya South Sumatra. The crossingcombinations were Pidie x Medan, Curup x Lampung, Pidie x Lampung, Lampung x Pidie, Curup x Medan, Indralaya xPontianak, Medan x Palembang, Curup x Pidie, and Jogya x Komering. Oil production, nitrate reductase enzyme activity,leaf chlorophyll content and relative plant growth rate were evaluated. The result showed that the relative plant growth ratecould be used as early detection parameter for yield potential. Progenies of Pontianak x Indralaya, Palembang x Indralayaand Pidie x Lampung were selected as promising hybrids based on high productivity and heterosis effect.Keywords: Jatropha curcas, heterosis, relative plant growth rate, nitrate reductase activity